2021
DOI: 10.1002/chem.202103709
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Thiol/Thiophenol Molecule‐Modulated Plasmon‐Mediated Silver Oxidation with Dark‐Field Optical Microscopy

Abstract: Surface plasmon can trigger or accelerate many photochemical reactions, especially useful in energy and environmental industries. Recently, molecular adsorption has proven effective in modulating plasmon-mediated photochemistry, however the realized chemical reactions are limited and the underlying mechanism is still unclear. Herein, by using in situ dark-field optical microscopy, the plasmonmediated oxidative etching of silver nanoparticles (Ag NPs), a typical hot-hole-driven reaction, is monitored continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As reported, molecules near plasmonic nanostructures become much more active in many chemical reactions due to the improved light absorption, electromagnetic field, local temperature, and hot carrier excitation [20][21][22] . In addition, the lifetime of plasmon-generated hot carriers can be prolonged obviously at the plasmon-molecule interface 22,23 .…”
mentioning
confidence: 92%
“…As reported, molecules near plasmonic nanostructures become much more active in many chemical reactions due to the improved light absorption, electromagnetic field, local temperature, and hot carrier excitation [20][21][22] . In addition, the lifetime of plasmon-generated hot carriers can be prolonged obviously at the plasmon-molecule interface 22,23 .…”
mentioning
confidence: 92%
“…Reproduced with permission from Ref. [110] (Copyright 2021 WILEY-VCH). B. R. C. de Menezes et al reported the preparation of acidand amine-functionalized CNTs and evaluated their dispersibility in four solvents with different polarities (water, ethanol, acetone, and xylene) to correlate the degree of dispersion of CNTs with their polarity.…”
Section: Figure 16mentioning
confidence: 99%
“…In addition to the semiconductor–plasmon interface, the plasmon–molecule interface can also be used to separate the plasmon-generated hot carriers. The plasmon–molecule interfaces can be constructed much more easily and conveniently by adsorbing molecules on plasmonic metals physically or chemically. Moreover, the matching of energy levels between those of plasmonic metal and adsorbed molecules can be readily and precisely controlled by altering the chemical structure and/or substitution group of the adsorbed molecules.…”
Section: Introductionmentioning
confidence: 99%